1996
DOI: 10.1079/bjn19960114
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism underlying the inhibitory effect of high calcium carbonate intake on iron bioavailability from ferrous sulphate in anaemic rats

Abstract: The influence of high CaCO, intake on the bioavailability of Fe from FeSO, was assessed during Fe repletion of rats with Fe-deficiency-induced anaemia. Fe-deficient rats with a mean blood haemoglobin concentration of 4.1 mmol/l were fed on purified Fe-adequate diets containing either 6.2 or 25.0 g CaCO,/kg (ten rats per group). Haemoglobin repletion after 14 d was significantly depressed by high CaCO, intake (9.5 v. 9.8 mmol/l for high and low CaCO, intake respectively; P = 0.03), as was apparent Fe retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
2
25
1
1
Order By: Relevance
“…Twelve 3-month-old male conventional Wistar rats (U: WU) were obtained from the Central Animal Facility of Utrecht University. This age group was chosen to be comparable with results published previously (Wienk et al, 1996). The doves and mynahs were kept in wire-mesh cages (1 ´0.6 ´1 m 3 ) as six birds per cage.…”
Section: Animals Housing and Dietmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve 3-month-old male conventional Wistar rats (U: WU) were obtained from the Central Animal Facility of Utrecht University. This age group was chosen to be comparable with results published previously (Wienk et al, 1996). The doves and mynahs were kept in wire-mesh cages (1 ´0.6 ´1 m 3 ) as six birds per cage.…”
Section: Animals Housing and Dietmentioning
confidence: 99%
“…The doses of radiolabelled tracers were based on earlier studies in rats and birds, which demonstrated that 59 Fe was a good marker for following the absorption of iron (Ward et al, 1991;Cork et al, 1995;Wienk et al, 1996;Santos et al, 1997). Chromium ( 51 Cr) was chosen as the non-absorbable marker because it is not absorbed from the intestinal lumen (Hudson et al, 1971;Stevens, 1988) and it has the same transit time as iron (Marx, 1979;Wienk et al, 1996).…”
Section: Radioactivity Tests and Measurement Smentioning
confidence: 99%
See 3 more Smart Citations